Randomised placebo controlled multicentre trial to assess short term clarithromycin for patients with stable coronary heart disease: CLARICOR trial. Issue 7532 (8th December 2005) - Jespersen, Christian M; Als-Nielsen, Bodil; Damgaard, Morten; Hansen, Jørgen Fischer; Hansen, Stig; Helø, Olav H; Hildebrandt, Per; Hilden, Jørgen; Jensen, Gorm B; Kastrup, Jens; Kolmos, Hans Jørn; Kjøller, Erik; et al.
Abstract: Objective To determine if the macrolide clarithromycin affects mortality and cardiovascular morbidity in patients with stable coronary heart disease. Design Centrally randomised multicentre trial. All parties at all stages were blinded. Analyses were by intention to treat. Setting Five Copenhagen University cardiology departments and a coordinating centre. Participants 13 702 patients aged 18 to 85 years who had a discharge diagnosis of myocardial infarction or angina pectoris in 1993–9 and alive in August 1999 were invited by letter; 4373 were randomised. Interventions Two weeks' treatment with clarithromycin 500 mg/day or matching placebo. Main outcome measures Primary outcome: composite of all cause mortality, myocardial infarction, or unstable angina pectoris during three years' follow-up. Secondary outcome: composite of cardiovascular mortality, myocardial infarction, or unstable angina pectoris. The outcomes were obtained from Danish registers and were blindly assessed by the event committee. Results 2172 participants were randomised to clarithromycin and 2201 to placebo. We found no significant effects of clarithromycin on the primary outcome (hazard ratio 1.15, 95% confidence interval 0.99 to 1.34) or secondary outcome (1.17, 0.98 to 1.40). Mortality was significantly higher in the clarithromycin arm (1.27, 1.03 to 1.54; P = 0.03) as a result of significantly higher cardiovascular mortality (1.45, 1.09 to 1.92; P = 0.01). Conclusions Short term clarithromycin in patients with stable coronary heart disease may cause significantly higher cardiovascular mortality. The long term safety of clarithromycin in patients with stable ischaemic heart disease should be examined. Trial registration ClinicalTrials.gov NCT00121550 .